A farewell to the Yahwist? : the composition of the Pentateuch in recent European interpretation - Dozeman, Thomas B.; Schmid, Konrad, 1965- (Symposium series (Society of Biblical Literature) ;, 2006)
Since the "assured results" of scholarship are rarely certain, it should come as no surprise that the classical formulation of the Documentary Hypothesis has yet again been called into question. However, many North American scholars are unfamiliar with the work of a new generation of European scholars who are advancing an alternate view of the compositional history of the Pentateuch. A growing consensus in Europe argues that the larger blocks of pentateuchal tradition, especially the stories of the patriarchs and Moses, were not redactionally linked before the Priestly Code, as the J hypothesis suggests, but existed side by side as two independent, rival myths of Israel's origins. This volume makes available both the most recent European scholarship on the Pentateuch and its critical discussion. --From publisher's description